2003
DOI: 10.1034/j.1600-0420.2003.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetic retinopathy by non‐ophthalmologists: an effective public health tool

Abstract: ABSTRACT.Purpose: To investigate and report the reliability of detection and grading of diabetic retinopathy by direct ophthalmoscopy through a dilated pupil by general physicians (non-ophthalmologists) and optometrists who have undergone a short period of training. Methods: A total of 400 eyes of 200 diabetes patients were examined by two non-ophthalmologists. Their observations were compared with an ophthalmologist's diagnoses for the same patients. Results: The diagnoses made by the general physician (kappa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
1
28
0
1
Order By: Relevance
“…Investigators concluded that only 5% of optometrists met the existing standards for DR screening programmes (sensitivity=0.80, specificity=0.95) 28. Our review found little information on the performance of non-medical graders in detection of DR,24 or on grading in LMICs,23 and no prior publications on non-medical graders in LMICs.…”
Section: Discussionmentioning
confidence: 76%
“…Investigators concluded that only 5% of optometrists met the existing standards for DR screening programmes (sensitivity=0.80, specificity=0.95) 28. Our review found little information on the performance of non-medical graders in detection of DR,24 or on grading in LMICs,23 and no prior publications on non-medical graders in LMICs.…”
Section: Discussionmentioning
confidence: 76%
“…Retinopathy lesions (microaneurysms, haemorrhages, cotton wool spots, hard exudates) are well known to doctors, and can be reliably detected using the direct ophthalmoscope available in most emergency departments and doctors’ offices 5. People with diabetes have regular fundus examinations in order to detect sight-threatening retinopathy lesions in a timely manner.…”
mentioning
confidence: 99%
“…The previous system included the referral of all diabetes patients to the hospital, retinography by a technician, and the study of all images and subsequent reporting by an ophthalmologist 1315. The inclusion of general practitioners in the screening program might help us to avoid excessive referrals of patients to hospital.…”
Section: Discussionmentioning
confidence: 99%